2018
DOI: 10.5539/ijps.v10n2p25
|View full text |Cite
|
Sign up to set email alerts
|

Application of Standardized Observation Form in School Counselling in Taiwan: Exploratory Study with Children Exhibiting Internalizing and Externalizing Behavior Concerns

Abstract: The exploratory study investigated the impact of Child-Centered Play Therapy (CCPT) on children who present with internalizing and externalizing behavioral concerns through a single-case design. Two second-grade male children in northern Taiwan displaying clinical levels of internalizing or externalizing behavior problems underwent 9 weeks of weekly 40-minute CCPT sessions. The children's parents and teachers completed the Child Behavior Checklist and Teacher's Report Form before and after play therapy. Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…These results coincide with studies that demonstrated the strength of CCPT in managing externalizing problems (Bratton et al, 2013;Cochran et al, 2017;Garza & Bratton, 2006;Nordling & Guerney, 1999). The once-weekly CCPT structure for handling externalizing problem behaviors as found effective by Schumann (2010), Ray et al (2017) and Tsai (2018) was likewise seen in this study. CCPT in a brief or short-term structure similar to those studied by previous researchers (Blanco et al, 2012;Bratton & Ray, 2000;Kaduson & Schaefer, 2006;Ray, 2008) suggest that there are indeed gains from such an intervention even at a short span of time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results coincide with studies that demonstrated the strength of CCPT in managing externalizing problems (Bratton et al, 2013;Cochran et al, 2017;Garza & Bratton, 2006;Nordling & Guerney, 1999). The once-weekly CCPT structure for handling externalizing problem behaviors as found effective by Schumann (2010), Ray et al (2017) and Tsai (2018) was likewise seen in this study. CCPT in a brief or short-term structure similar to those studied by previous researchers (Blanco et al, 2012;Bratton & Ray, 2000;Kaduson & Schaefer, 2006;Ray, 2008) suggest that there are indeed gains from such an intervention even at a short span of time.…”
Section: Discussionsupporting
confidence: 81%
“…What may be considered short-term CCPT ranges from 10 to 12 weekly sessions or shorter, which has been shown to be effective for school-related, emotional and behavioral problems (Guerney, 2001; Landreth, 2012). Significant decreases in externalizing and internalizing problem behaviors were also found when CCPT was administered in nine 40-min sessions on a weekly basis (Tsai, 2018). In high poverty schools, a nine-session CCPT frame yielded moderate to large effects for externalizing problems, total problems, attention problems, and learning-related self-efficacy (Cochran et al, 2017).…”
Section: Structure Of Ccpt Sessionsmentioning
confidence: 99%